THE CONCEPT OF SEMANTIC FIELD IN LINGUISTICS (Academicia Globe: Inderscience Research, 2022)
The article considers the generality, the similarity between the elements that make up the semantic field. The words on this basis are combined into a lexico-semantic. In this respect, they differ fundamentally from groups. In our article, ideological dictionaries are a fundamental source for studying the meaning and content of words, their semantic field.